please answer this question
Attachments:
![](https://hi-static.z-dn.net/files/d8c/dc18718afecdbc70decf97419beef5f2.jpg)
Answers
Answered by
1
6^x × 6^ (4-3x) = 6^-18
6 ^ (-2x + 4 ) = 6 ^ -18
-2x + 4 = - 18
-2x = -22
x = 11 Ans.
nishant7119:
thanks
Answered by
0
Answer:
11 is right answer.........
Attachments:
![](https://hi-static.z-dn.net/files/d5f/74458580100a6f8ff24276d1a3f35b4b.jpg)
Similar questions
History,
7 months ago
Social Sciences,
7 months ago
History,
7 months ago
Math,
1 year ago
English,
1 year ago